Réinvestir le saltus dans la pensée agronomique moderne : vers un nouveau front eco-politique ? - Xavier Poux; Jean-Baptiste Narcy; Blandine Ramain (L'Espace Politique)
Biodiversity is increasingly recognised by politicians and citizens as a major issue. In the European context, its future depends on a large share on agriculture, leading whether to destruction or conservation. In this context, European and national policies are now reconsidering objects that have been largely hampered during the last decades: meadows, wetlands, hedges etc. While they have been put away from agricultural extension and agronomic research, such elements are now core-issues in new environmental approaches such as ecological landuse (or compensatory environmental areas) and ecological corridors or networks. In the French context, the Grenelle de l’environnement is being promoting a so-called “green and blue corridor” (“trame verte et bleue”) as a key-reference for spatial planning at different levels. Such corridor should incorporate the above-mentioned agricultural features, forming altogether the semi-natural vegetation (SNV).One could interpret this shift as a come-back of the saltus (from the ancient trilogy ager [= cultivated land], silva [= forested land] and saltus [=between the two formers, open and uncultivated land formed of herbaceous vegetation or low height scrubs]), as the ecological objects aimed at in environmental policies are indeed components of saltus. Nevertheless, while SNV and saltus virtually apprehend the same objects, they conceptually are quite different. Saltus should be understood in its overall relationship with ager and silva and through its historical and agricultural perspective. SNV is, conceptually, easily seen apart from the agricultural matrix it is put into, as an alien feature inherited from the past but with no present and future agronomic function. Thus, its management rationale is unclear, which is a paradox while its place in the policy debate is gaining importance. This understanding of SNV leads to a policy front opposing the agricultural and the environmental worlds, the stake being the land sharing resulting from the confrontation.Meanwhile, agronomists are proposing models based on the ager, in which the saltus is marginalised if not denied, and the only species taken into account are selected crops or animals and useful auxiliaries. Thus, on the one hand we have a saltus hosting biodiversity, but fundamentally belonging to the past; on the other hand, an ager that pretends to manage biodiversity, but without considering the whole set of wild species and habitats.Revisiting the concept of saltus, seen as an useful grid to understand the developments of agriculture and biodiversity at the European level, is proposed in this paper. The point is to apprehend the future of the biodiversity linked to agriculture in light of its past, in order to better understand the long term factors at play.